Izdelava poslovnih poročil, izjav o upravljanju ter izjav o nefinančnih informacijah v konsolidiranih letnih poročilih in letnih poročilih posameznih gospodarskih družb - Bratina, Borut (Podjetje in delo, 2017)
Members of a company's management and control bodies shall jointly ensure that annual reports (accounting part and business report) with all component parts, including the corporate governance statement and non-financial statement, are in accordance with legislation and accounting standards. All members of a company's management body shall confirm this by signing the annual report and the component parts (Article 60a of the Companies Act % ZGD-1). The last amendments of the Companies Act - ZGD-1I and ZGD-1J - have introduced new developments into the content, the component parts and appendices of business reports in accordance with the legislation of the European Union. These are the corporate governance statement, non-financial statement and report about the relationships with controlling companies. The role of an auditor has also increased significantly. The auditor has to review both statements and appendices, and present his findings. The goal of these new developments is to increase socially responsible governance of companies.